Evaluation of No-Touch Technologies for Decontamination of Toys in Pediatric Healthcare Settings. (5th January 2021) - Haydar, Hanan; Kumar, Jessica A; Cadnum, Jennifer L; Zangla, Emily; Hoyen, Claudia K; Donskey, Curtis J
Abstract: No-touch technologies could be useful to decontaminate shared toys in healthcare settings. A high-level disinfection cabinet and electrostatic sprayer were effective against methicillin-resistant Staphylococcus aureus (MRSA), bacteriophage MS2, and Clostridioides difficile spores on toys. An ultraviolet-C light box was less effective but reduced MRSA and bacteriophage MS2 by >2 log10 .